Maximizing The Production Quality of Presto Milkfish in Juata Through Six Sigma Method Implementation - Hidayat, Nurul; Wibowo, Devina Novelly; Clarisa, Cafita; Pratama, Ordinaryo (Manunggal Halim Jaya, 2025)
The purpose of this study is to analyze the implementation of quality control system in the presto milkfish production process and identify factors that affect the quality of the final product. The research was conducted using Six Sigma methodology. The research shows that there are several important points in the manufacturing process that affect the quality of the final product. Factors that contribute to quality degradation include cooking time variation, process temperature variation, raw material quality, and operator skills. By implementing a quality control system on the production process that includes standardization of the production process, inspection of raw materials, operator training, regular monitoring, and reduction of defects in milkfish. This study provides recommendations for continuous improvement in the presto milkfish production system to maintain product quality consistency.